Mechanisms and Performance of Composite Joints Through Adhesive and Interlocking Means—A Review - Davaasambuu, Khishigdorj; Dong, Yu; Pramanik, Alokesh; Basak, A.K. (MDPI, 2025)
Conventional adhesively bonded joints, such as single-lap, curved-lap, wavy-lap, double-lap, stepped-lap, and scarf joints, are widely used for aerospace, automotive, and medical applications. These adhesively bonded joints exhibit different load transfer mechanisms and stress distributions within adhesive layers, which depend primarily on their geometries and mechanical properties of bonded materials. As such, joint geometry and material properties play a critical role in determining the capability of the joints to withstand high loads, resist fatigue, and absorb energy under impact loading. This paper investigates the effects of geometry and material dissimilarity on the performance of both conventional bonded and interlocking joints under tensile loading based on the information available in the literature. In addition, bonding and load transfer mechanisms were analysed in detail. It was found that stress concentration often occurs at free edges of the adhesive layer due to geometric discontinuities, while most of the load is carried by these regions rather than its centre. Sharp corners further intensify resulting stresses, thereby increasing the risk of joint failure. Adhesives typically resist shear loads better than peel loads, and stiffness mismatches between adherents induce an asymmetric stress distribution. Nonetheless, similar materials promote symmetric load sharing. Among conventional joints, scarf joints provide the most uniform load distribution. In interlocking joints such as dovetail, T-slot, gooseneck, and elliptical types, the outward bending of the female component under tension can lead to mechanical failure